PENGARUH NETWORKING, KELENGKAPAN INFORMASI PEMASARAN TERHADAP MARKET ENTRY STRATEGY QUALITY DALAM UPAYA MENINGKATKAN MARKETING PERFORMANCE UMKM DI SEMARANG - Teguh Ariefientoro; Nina Ernawati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
Companies (including SMEs) is required to be able to maintain its existence and face the forces or factors of competition (five forces) that is a competitor in the same company, bargaining power of suppliers, bargaining power of buyers, threat of new entrants and threat of substitute products (Porter, 1996). Therefore, the company should have adequate management and strategy. This means that the company must have a competitive advantage, among others, in the areas of technology, product quality, quality of personnel, capital, price, cost-efficient and satisfactory service quality.The purpose of this study was (a). analyze the effect of networking on market entry strategy quality; (b). analyze the effect of marketing on the completeness of information quality and market entry strategy (c). analyze the effect of market entry strategy to marketing quality performance of SMEs in Semarang. While the Research Contributions (a). Provide feedback to the SME entrepreneurs in Semarang in improving marketing performance through increased market entry strategy for quality; (b) Provide feedback to the Government of Semarang in determining the policies / regulations to encourage the development of a product business, especially SMEs; and (c) To contribute in the field of scientific marketing strategies (marketing strategy) that proved empirically. This research is exploratory, descriptive and causal, which requires the support of research, testing and development of the conceptualization of the latest facts. The population of this study are the owner or manager of SMEs in Semarang. Data analysis techniques: (a). Descriptive analysis to determine the general perception of respondents regarding the variables studied; (b). Hypothesis testing is performed with multiple regression is used to test the structural equation model (SEM).The research results showed that the completeness of the information networking and marketing a positive effect on quality Market entry strategy. Market entry strategy for quality also has positive influence on Marketing Performance. This study failed to find that Market entry strategy can also affect the quality Performance Marketing. It can be concluded that SMEs who want to improve their Performance Marketing need to build a better Market entry strategy qualiyt her to reliable by SMEs.